Torsional vibration characteristics and experimental study of cracked rotor system with torsional oscillation. (October 2020) - Liu, Chao; Jiang, Dongxiang
Highlights: Experiments on the transverse and slant cracked rotors with torsional oscillation. Torsional vibration measured and used for comparing features of cracked rotors. Dynamic analysis on transverse and slant cracks for comparison with experiments. Vibration features of the transverse and slant cracked rotor system are discussed. Abstract: Root causes of numerous crack failures are attributed to the torsional oscillation between the turbine generator and the grid. To prevent such kind of failures, torsional vibration monitoring system has been intensively installed in reality and the torsional vibration is more and more observed in the operation. However, the mechanism of the characteristics of torsional vibration of the rotor system with and without cracks has not been well explored. Therefore this work presents the dynamic analysis and experimental study on the rotor system with transverse and slant cracks. For simulating the torsional oscillation in reality, excitation device is designed in the experiments and torsional vibration is measured. Based on this, the characteristics of lateral and torsional vibration of the rotor system are compared. The results show that, (i) although the slant crack presents more significant later-torsional vibration (especially for the breathing crack), the transverse cracked rotor system show higher amplitudes in the fundamental frequency and harmonic components (especially for the open crack) and (ii) the torsional excitation introduces more obvious vibration fluctuation in the rotor system with cracks (observed from the orbits and the torsional vibration).